Sítio histórico urbano de Santa Leopoldina : uma análise de sua preservação - Morelato, Andressa da Silveira (2013)
The present work was conceived from the interest to analyze the conservation efforts performed in Santa Leopoldina-ES historical site, a listed preserved area since 1983, as “Conjunto Arquitetônico de Santa Leopoldina” (or Santa Leopoldina architecture co